Question
upstudy study bank question image url

Find \( f+g, f-g, f g \) and \( \frac{f}{g} \). Determine the domain for each function. \( f(x)=5 x+2, g(x)=x-6 \) \( (f+g)(x)=\square \) (Simplify your answer.)

Ask by Garza Schultz. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( (f+g)(x) = 6x - 4 \)

Solution

Divide the polynomials by following steps: - step0: Using Long Division to Divide Polynomials: \(\frac{\left(5x+2\right)}{\left(x-6\right)}\) - step1: Calculate: \(5+\frac{32}{x-6}\) Calculate or simplify the expression \( (5*x + 2) + (x - 6) \). Simplify the expression by following steps: - step0: Solution: \(\left(5x+2\right)+\left(x-6\right)\) - step1: Remove the parentheses: \(5x+2+x-6\) - step2: Add the terms: \(6x-4\) Calculate or simplify the expression \( (5*x + 2) - (x - 6) \). Simplify the expression by following steps: - step0: Solution: \(\left(5x+2\right)-\left(x-6\right)\) - step1: Remove the parentheses: \(5x+2-\left(x-6\right)\) - step2: Remove the parentheses: \(5x+2-x+6\) - step3: Subtract the terms: \(4x+8\) Calculate or simplify the expression \( (5*x + 2) * (x - 6) \). Simplify the expression by following steps: - step0: Solution: \(\left(5x+2\right)\left(x-6\right)\) - step1: Apply the distributive property: \(5x\times x-5x\times 6+2x-2\times 6\) - step2: Multiply the terms: \(5x^{2}-30x+2x-12\) - step3: Add the terms: \(5x^{2}-28x-12\) Let's calculate \( f+g \), \( f-g \), \( fg \), and \( \frac{f}{g} \) step by step. 1. **Finding \( f+g \)**: \[ (f+g)(x) = f(x) + g(x) = (5x + 2) + (x - 6) = 6x - 4 \] 2. **Finding \( f-g \)**: \[ (f-g)(x) = f(x) - g(x) = (5x + 2) - (x - 6) = 4x + 8 \] 3. **Finding \( fg \)**: \[ (fg)(x) = f(x) \cdot g(x) = (5x + 2)(x - 6) = 5x^2 - 30x + 2x - 12 = 5x^2 - 28x - 12 \] 4. **Finding \( \frac{f}{g} \)**: \[ \left(\frac{f}{g}\right)(x) = \frac{f(x)}{g(x)} = \frac{5x + 2}{x - 6} = 5 + \frac{32}{x - 6} \] Now, let's determine the domain for each function: - **Domain of \( f+g \)**: Since both \( f(x) \) and \( g(x) \) are polynomials, their sum \( 6x - 4 \) is also a polynomial. The domain is all real numbers: \( \mathbb{R} \). - **Domain of \( f-g \)**: Similarly, \( 4x + 8 \) is a polynomial, so the domain is all real numbers: \( \mathbb{R} \). - **Domain of \( fg \)**: The product \( 5x^2 - 28x - 12 \) is a polynomial, thus the domain is all real numbers: \( \mathbb{R} \). - **Domain of \( \frac{f}{g} \)**: The function \( \frac{5x + 2}{x - 6} \) is defined for all \( x \) except where the denominator is zero. Thus, the domain is \( x \neq 6 \) or in interval notation: \( (-\infty, 6) \cup (6, \infty) \). In summary: - \( (f+g)(x) = 6x - 4 \) - \( (f-g)(x) = 4x + 8 \) - \( (fg)(x) = 5x^2 - 28x - 12 \) - \( \left(\frac{f}{g}\right)(x) = 5 + \frac{32}{x - 6} \) **Domains**: - \( f+g \): \( \mathbb{R} \) - \( f-g \): \( \mathbb{R} \) - \( fg \): \( \mathbb{R} \) - \( \frac{f}{g} \): \( (-\infty, 6) \cup (6, \infty) \)

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

To find \( f+g \), we combine the functions \( f(x) \) and \( g(x) \): \[ (f+g)(x) = f(x) + g(x) = (5x + 2) + (x - 6) = 6x - 4 \] Now for \( f-g \): \[ (f-g)(x) = f(x) - g(x) = (5x + 2) - (x - 6) = 5x + 2 - x + 6 = 4x + 8 \] Next, we calculate \( f g \): \[ (f g)(x) = f(x) \cdot g(x) = (5x + 2)(x - 6) = 5x^2 - 30x + 2x - 12 = 5x^2 - 28x - 12 \] For \( \frac{f}{g} \): \[ \left(\frac{f}{g}\right)(x) = \frac{f(x)}{g(x)} = \frac{5x + 2}{x - 6} \] Now, let's determine the domains for each function. 1. \( f + g \) and \( f - g \) are polynomials, so their domains are all real numbers: \( (-\infty, \infty) \). 2. \( f g \) is also a polynomial, and its domain is all real numbers: \( (-\infty, \infty) \). 3. \( \frac{f}{g} \) is a rational function, and the domain is all real numbers except where \( g(x) = 0 \). Since \( g(x) = x - 6 \), we have \( x \neq 6 \). Thus, the domain is \( (-\infty, 6) \cup (6, \infty) \). So we summarize: - \( (f+g)(x) = 6x - 4 \) - \( (f-g)(x) = 4x + 8 \) - \( (f g)(x) = 5x^2 - 28x - 12 \) - \( \left(\frac{f}{g}\right)(x) = \frac{5x + 2}{x - 6} \) Domains: - \( f+g \) and \( f-g \): \( (-\infty, \infty) \) - \( f g \): \( (-\infty, \infty) \) - \( \frac{f}{g} \): \( (-\infty, 6) \cup (6, \infty) \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy